1996
DOI: 10.1021/ac960044j
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography/Chemical Reaction Interface Mass Spectrometry as an Alternative to Radioisotopes for Quantitative Drug Metabolism Studies

Abstract: Chemical reaction interface mass spectrometry (CRIMS) was coupled on-line with HPLC using a Vestec particle beam interface. A helium-assisted nebulizer provided added stability with no loss in accuracy or precision as compared to the thermospray nebulizer at flow rates of up to 1.0 mL/min using isocratic conditions. However, mass spectral response was found to be solvent-dependent for both the helium-assisted and thermospray nebulizers. Postcolumn solvent addition of methanol eliminated solvent-dependent decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 17 publications
(27 reference statements)
1
39
0
Order By: Relevance
“…The urine results showed a ␦ 13 C value 2.8‰ above the control 13 C/ 12 C ratio using a 1% aliquot (8 -16 mL) of a 24 h human urine sample. This elevated ratio converts to detecting an 83 Ϯ 52% excretion of the administered 13 C aspirin dose into urine. Nakagawa et al [2] measured ␦ 13 C and ␦ 15 N in rat urine, feces, liver, and hair, again by combustion and measurement of the resulting CO 2 and N 2 by IRMS.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…The urine results showed a ␦ 13 C value 2.8‰ above the control 13 C/ 12 C ratio using a 1% aliquot (8 -16 mL) of a 24 h human urine sample. This elevated ratio converts to detecting an 83 Ϯ 52% excretion of the administered 13 C aspirin dose into urine. Nakagawa et al [2] measured ␦ 13 C and ␦ 15 N in rat urine, feces, liver, and hair, again by combustion and measurement of the resulting CO 2 and N 2 by IRMS.…”
mentioning
confidence: 82%
“…We can detect trace amounts of a 13 C-labeled drug (3Ј-azido-3Ј-deoxythymidine, AZT) in urine or feces. Our ability to quantify less than 100 ng/mL of excess 13 C (ϳ1 g/mL of 13 C-labeled AZT) from a sample equivalent to 10 L of urine is superior to previous detection limits for 13 C in urine that use off-line combustion methods. Parallel studies using 14 C-labeled AZT showed that our stable isotope method provides comparable percent excretion data for urine and feces.…”
mentioning
confidence: 90%
See 3 more Smart Citations